Investigating the Health-related Quality of Life in Hepatitis C Patients with Liver Cirrhosis Using Oral Antivirals, Before and after the Treatment - Haghighat, Sahar; Salimi Akinabadi, Atefe; Zandi, Mitra; Halimi, Aram; Bana Derakhshan, Homayoon; Al-Yateem, Nabeel; Momani, Aaliyah; Mosavi Jarrahi, Alizera; Maria Dias, Jacqueline (Asian Pacific Journal of Cancer Biology, 2024)
Objectives: Liver Cirrhosis is a debilitating chronic complication of many liver diseases including hepatitis C virus infection. Oral treatment of anti-viral infection can have effect alleviation this complication. The present study was conducted to measure the effect of oral antiviral treatment on the health-related quality of life in the patients with chronic hepatitis C. Methods: A before and after the treatment intervention setting clinical trial was setup. Patients included cases of clinically hepatitis C with liver cirrhosis. Oral antiviral drugs were administrated as intervention. The quality of life was measured using Chronic liver disease questionnaire (CLDQ) before treatment and after treatment. Patient demographics, treatment information, and HRQoL scores were collected. Results: A total of 65 patients with hepatitis C and liver cirrhosis were included in the study. The mean score of the patients’ quality of life and all its dimensions, 12 weeks after treatment with oral antiviral drugs, was on average 23.59 points higher than before, and this difference was significant (p<0.001). Significant improvements were observed in all dimensions of HRQoL, including emotions, worries, systemic symptoms, abdominal symptoms, activity, and fatigue (p < 0.001). No significant correlations were found between the mean difference in HRQoL scores and age or disease duration (p > 0.05). Conclusions: The present study shows that the use of oral antiviral drugs can improve the health-related quality of life. Health care providers can use the results of the study to plan regarding the treatment and care measures which increase the quality of life in hepatitis C patients.